Korelasi Pemberian Tugas Rumah Terhadap Prestasi Belajar Mahasiswa Program Studi Diploma 3 Bahasa Jepang Universitas Sam Ratulangi - Moniung, Ilke Janemralina (Universitas Sam Ratulangi, 2017)
Homework method is one of the method in gaining understanding. It is a way in increasing the learning result mastery, the phase is important because the lecturer will get a helpful feedback from the students regarding the learning process. A quick task given with a good learning outcome can increase the ability of student in wider, higher and complex learning experience.A regular task given will give a good attitude and positive way of learning, and eventually will motivate the students to have independent study habit of learning and studying. Therefore, task giving activity still trigger the learning ability of the students. The receiving attitude of students in responding of the task is needed to be focused. The diligent students will adjust to that environment easily while others will not. The reverse attitude are shown by the lazy students, task given activities will be a burden to them. They reject directly and act without attention. In other words, the diligent students will do the tasks and the lazy student will not do the tasks or even they do the tasks unseriously. Efforts are needed in improving the Japanese students study achievements one of the efforts is giving the student homework regularly and expecting it can stimulate the students eagerness to study at homework that will increase the study achievement. This research is aimed to find the significance correlation between homework given and study achievement of students who study Japanese.Data were collected by test, quesionare, interview, observation and dokumentation. Keyword: Homework, study, achievement